Cancellation of birefringence in DBR laser through principal axis offset by a rotation of 90° - Zaini, Muhammad Khairol Annuar; Lai, Man Hong; Islam, Md. Rajibul; Lim, Kok Sing; Ahmad, Harith (Springer Verlag (Germany), 2018)
The cancellation of birefringence in the distributed Bragg reflector based on 90° rotation offset method is demonstrated. It is found that the birefringence, which causes the peak bifurcation has been eliminated and a single peak is produced at each resonance in the output spectrum. This modification is an economic solution for eliminating the birefringence of the optical fibre devices.